Pelatihan dan Pendampingan Penggunaan Aplikasi Digital dalam Perencanaan Bisnis dan Keuangan BUMDes - Ahmad Faisol; Sipa Paujiah; Edwin Russel; Mudji Rachmat Ramelan (Jurnal Abdimas Multidisiplin, 2022)
Purpose: The purpose of this activity is to improve the ability of Village-Owned Enterprises (BUMDes) managers in preparing financial plans, in the form of assessing feasibility studies, analysing income and expenses, and preparing financial transactions using digital technology. Research methodology: The method used in this community service activity is counselling, training and mentoring. The target of the activity is Village administrators and Village-Owned Enterprises (BUMDes). Results: The results of this community service activity is to increase knowledge about making financial report, increase knowledge about business plan, increase knowledge about feasibility studies, and increase knowledge about business digital technology. Conclusions: After the activity is carried out, the community gains knowledge, insight and understands the benefits of managers in preparing financial plans, managers in preparing financial plans, managers in preparing business plan, in the form of assessing feasibility studies, and using business digital technology. Limitations: The ability of village officials in the use of technology. Contribution: This service is useful for village officials and BUMDes administrators in choosing businesses that are in accordance with the potential of their village.